Magnetic Resonance Imaging Findings in Patients with Low Back Pains and its Associations with Demographic Variables and Body Mass Index in Onitsha Nigeria - Ogolodom, Michael Promise; Ugwuanyi, Daniel C.; Onwuka, Michael Chijioke; Egbeyemi, Oluwafemi Olumide; Chiaghanamm, Ndubuisi O.; Omita, Efe; Okon, Idara Asuquo; Nwadike, Sharonrose Ogochukwu; Brownson, Egop Egop (European Scientific Journal, ESJ, 2022)
Background: Low back pain (LBP) is arguably the most prevalent musculoskeletal condition found among both developed and developing nations. This study was designed to evaluate the MRI findings in patients with LBP and its association with the patients’ age, gender, and anthropometric variables in Onitsha, Anambra State, Nigeria. Materials and Methods: This was a retrospective cross-sectional study carried out from June 2021 to August 2021 at the MRI unit of the radiology department of a private diagnostic center in Onitsha Anambra state, Nigeria. A total of 76 MRI reports were selected based on the inclusion criteria of this study, which include reports with LBP clinical indication, radiological findings, and complete patient demographic (age and gender) and anthropometry (weight and height) variables. Results: The majority 42 (53.3%), were males when compared with their female counterparts 34 (44.7%). A greater number, 22(28.9%) of the patients were within the age bracket of 51-60 years, and the least 2(2.6%) were within the age group of 21-30 years. Most 29(38.12%) of the patients had degenerative disc disease, and the least 2(2.63%) had osteoporosis. Conclusion: Male preponderance was noted in this study and majority of the case was seen in people within the sixth decade of life. Degenerative disc disease was the most common pathological entity identified in those presented for MRI due to LBP in our setting. There was a statistically significant mean difference in the MRI findings by age. There was no statistically significant mean difference in the MRI findings by gender.